Scaling up Information Services for Development: A Framework of Increasing Returns for Telecenters - TSCHANG, Ted (Institutional Knowledge at Singapore Management University, 2002)
Telecentres are an important type of information and communication technology (ICT) system particularly assisting rural and urban communities in developing countries, but the focus is often put on social development, sometimes on static economic returns, and rarely on dynamic economic aspects. This paper develops a basis for understanding the factors behind financial success in a dynamic setting based on the concept of increasing returns. This is applied to telecentres according to the stage of maturity of their information services. The framework is illustrated with literature- and interview-based cases, and will help an understanding of ways in which telecentres can scale-up their operation and impact.